Responses of antibiotic and heavy metal resistance genes to bamboo charcoal and bamboo vinegar during aerobic composting. (September 2019) - Guo, Honghong; Gu, Jie; Wang, Xiaojuan; Yu, Jing; Nasir, Mubasher; Peng, Huiling; Zhang, Ranran; Hu, Ting; Wang, Qianzhi; Ma, Jiyue
Abstract: The application of compost in agriculture has led to the accumulation of antibiotic resistance genes (ARGs) and heavy metal resistance genes (MRGs) in the soil environment. In this study, the response of ARGs and MRGs to bamboo charcoal (BC) and bamboo vinegar (BV) during aerobic composting was investigated. Results showed that BC + BV treatment reduced the abundances of ARGs and mobile genetic elements (MGEs) during the thermophilic period, as well as achieved the lowest rebound during the cooling period. BC + BV promoted the growth of Firmicutes, thereby facilitating the thermophilic period of composting. The rebound of ARGs and MGEs can be explained by increasing the abundance of Actinobacteria and Proteobacteria at the end of composting. Composting reduced the abundances of MRGs comprising pcoA, tcrB, and cueO, whereas cusA and copA indicated the selective pressure imposed by heavy metals on bacteria. The fate of ARGs was mainly driven by MGEs, and heavy metals explained most of the variation in MRGs. Interestingly, nitrogen conversion also had an important effect on ARG and MRG profiles. Our current findings suggest that the addition of BC + BV during compost preparation is an effective method in controlling the mobility of ARGs and MRGs, thereby reducing the environmental problems. Graphical abstract: Image 1 Highlights: BC plus BV treatment showed the highest reduction of ARGs and MGEs. Nitrogen conversion had an important effect on ARG and MRG profiles. Fate of ARGs was mainly driven by MGEs. cusA and copA confirmed the selection pressure of heavy metals.